Total ankle replacement in patients with haemophilic arthropathy: primary arthroplasty and conversion of painful ankle arthrodesis to arthroplasty. Issue 4 (17th March 2017) - Preis, M.; Bailey, T.; Jacxsens, M.; Barg, A.
Abstract : Introduction: There are two general surgical approaches for operative treatment of end‐stage haemophilic ankle arthropathy: ankle arthrodesis and total ankle replacement (TAR). Aim: The aim of this study was to determine intraoperative and postoperative complications and evaluate the mid‐term clinical and radiographic outcomes of TAR in patients with haemophilic arthropathy. Methods: Fourteen patients with a mean age of 51.4 ± 10.2 years (range = 32.9–63.7) were treated for end‐stage haemophilic ankle arthropathy. Nine procedures were primary arthroplasties, five procedures were conversions of painful ankle arthrodesis to TAR. The mean duration of follow‐up was 5.8 ± 2.3 years (range = 2.0–9.2). Component stability and alignment was assessed with weight‐bearing radiographs. Clinical assessment was performed. Results: One patient sustained an intraoperative medial malleolar fracture. In two patients, delayed wound healing was observed. In one patient, open arthrolysis was performed due to painful arthrofibrosis. Both components were neutrally aligned. Visual analogue scale (VAS) significantly decreased from 8.5 ± 0.9 (range = 8–10) to 1.3 ± 1.6 (range = 0–6). Significant functional improvement including range of motion (ROM) and American Orthopaedic Foot and Ankle Society (AOFAS) hindfoot score was observed. The summarized components of the SF‐36 physical and mental outcomes score significantly improved at the latest follow‐up. Complication rates and clinical/radiographic outcomes were comparable in patients with primary TAR and conversion of ankle arthrodesis to TAR. Conclusion: The mid‐term results following TAR or a conversion procedure in patients with haemophilic arthropathy are encouraging. However, for postoperative success, access to an experienced, multidisciplinary team including a haematologist is mandatory.